APRENDIZAGEM E SATISFAÇÃO DOS PARTICIPANTES DE CURSO À DISTÂNCIA PARA CONSELHEIROS DE ALIMENTAÇÃO ESCOLAR - Luisete Moraes Bandeira; Natacha Toral; Elisabetta Recine (Universidade do Estado do Rio de Janeiro, 2016)
Objective: To evaluate participants' learning and satisfaction in a distance learning training course for school feeding counselors, developed according to their socio-demographic characteristics and training needs. Methods: Scales to assess participants' satisfaction regarding the course and tutors were applied. Learning was assessed through diagnostic and summative assessments, pretest and posttest, and with a formative assessment at the end of each unit, with scales to assess participants in forums, case studies, practical activities, and multiple choice questions to evaluate document analysis activities. Results: The main topics included as training needs were bidding, submission of accounts and quality control of food products. There was great satisfaction with the course and tutors. In relation to learning, there was no significant difference between the average scores in the pretest and posttest, but the performance observed in the formative assessment was satisfactory. Conclusion: The evaluation of the counselors' socio-demographic data and training needs, along with proper planning, allowed the development of an interesting and feasible course, since satisfaction and learning rates among participants were high. We emphasize the importance of expanding low-cost training strategies like this, considering the high number of school feeding counselors in Brazil. DOI: 10.12957/demetra.2016.17447